The Dobbs Decision and Undergraduate Medical Education: The Unintended Consequences and Strategies to Optimize Reproductive Health and a Competent Workforce for the Future. (8th November 2022) - Stephenson-Famy, Alyssa; Sonn, Tammy; Baecher-Lind, Laura; Bhargava, Rashmi; Chen, Katherine T.; Fleming, Angela; Kang Morgan, Helen; Morosky, Christopher M.; Schaffir, Jonathan A.; Madani Sims, Shireen; Sutton, Jill M.; Royce, Celeste S.; et al.
Abstract : The June 2022 U.S. Supreme Court decision on Dobbs v Jackson Women's Health Organization resulted in state-specific differences in abortion care access across the country. The primary concern in the obstetrics and gynecology education community has been the impact on resident and fellowship training programs. However, the impact on undergraduate medical education and the broad implications for future generations of physicians are crucial to address. It is estimated that 48% of matriculants to MD-granting medical schools will receive their medical education in the 26 states with significant abortion restrictions or bans. Undergraduate medical educators need to continue to adequately teach the basic science, clinical care, and population health outcomes of reproductive medicine, including pregnancy and abortion. In addition, students in states with more restrictions on abortion will have less or no clinical exposure, and those in states with few restrictions may be excluded due to overcrowding of learners from restricted states. Students' own health care also needs to be considered, as access to abortion care for themselves or their partners may create applicant pool demographic shifts by state as applicants consider options for where to pursue their medical education. It is important to ensure that teaching of foundational science of pregnancy, abortion, and reproductive health continues throughout the United States. Undergraduate and graduate medical educators will need to closely monitor the downstream impact of decreased clinical exposure of abortion. Further study of the personal health impact of abortion care access for medical students and awareness of the changing applicant pool demographics by state is needed.